Laboratory and imaging studies used by French rheumatologists to determine the cause of recent onset polyarthritis without extra-articular manifestations. Issue 7 (1st July 2002) - Saraux, A; Maillefert, J F; Fautrel, B; Flipo, R M; Kaye, O; Lafforgue, P; Guillemin, F; Botton, E
Abstract : Background: The cause of recent onset polyarthritis can be difficult to identify. Objective: To determine which laboratory and imaging studies French rheumatologists recommend, not taking cost into account, for the diagnosis of recent onset polyarthritis without extra-articular manifestations. Methods: From the list of the French Society for Rheumatology, a random sample of 210 rheumatologists was selected, who were asked to complete a questionnaire on the laboratory and imaging studies they would recommend in two fictional cases of recent onset polyarthritis (possible rheumatoid arthritis (RA)—case 1 and probable RA—case 2). Results: In case 1, the following were recommended by over 75% of respondents: hand radiographs, rheumatoid factors (RFs), and antinuclear antibodies (ANA) (92%, 98%, and 98%, respectively). 50–74% of respondents recommended radiographs of the feet, knees, and chest (50%, 57%, and 66%, respectively); blood cell counts, erythrocyte sedimentation rate (ESR), serum assays of C reactive protein (CRP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (65%, 74%, 67%, and 62%, respectively). 25–49% recommended determination of creatinine and proteinuria, HLA-B27, antikeratin antibody, radiographs of the pelvis, and synovial fluid analysis. Several investigations were recommended less often in case 2 than in case 1. Nevertheless, some laboratory and imaging studies (radiographs of hand, feet, knees, chest x rays, blood cell counts, ANA, RF, antikeratin antibody, CRP, ESR, creatinine, AST and ALT, proteinuria, and joint aspiration) were recommended by more than 25% of respondents in both cases. Conclusion: Wide variations were found among rheumatologists, indicating a need for standardisation. Some laboratory and imaging studies are recommended by at least 25% of respondents in recent onset polyarthritis with or without clues suggesting RA. In contrast, many tests were considered useful by fewer than 25% of the respondents in both cases.